DETEKSI POTYVIRUS PADA NILAM (Pogostemon Cablin (BLANCO) BENTH) DENGAN TEKNIK ELISA DI SULAWESI TENGGARA - TAUFIK, MUHAMMAD; HASAN, ASMAR; KHAERUNI, ANDI; -, GUSNAWATY HS -; MAMMA, SARAWA (Jurnal Agroteknos, 2014)
Mosaic symptoms were observed on Patchouli (Pogostemon cablin) around North Kolaka and Kolaka, Southeast Sulawesi during surveys in early 2012. Indirect-ELISA based detection was conducted using symptomatic leaf samples. The objective of the research was to determine disease incidence of Potyvirus in several farms of Patchouli plant in Southeast Sulawesi. The results showed that Patchouli plant (Pogostemon cablin) was found to be infected with Potyvirus disease showing mosaic symptoms and malformation on the leaf samples i.e. in Amotowo and Boro-Boro Villages of subdistrict Boro-Boro, and Landabaro Village, Mowila subdistrict of South Konawe regency; Asinua Village of subdistrict Unaaha, Lambuya district of subdistrict Lambuya, and Bungguosu district, Konawe subdistrict of Konawe regency; and Anduonohu district, Poasia subdistrict of Kendari regency. This is the first report on Potyvirus infection on patchouli in Southeast Sulawesi. Keywords: Inderect-ELISA, mosaic, Potyvirus, Pogostemon cablin